Influence of indirect ultrasonic vibration on the microstructure and mechanical behavior of Al-Si-Cu alloy - Puga, Hélder (2013)
The influence of high intensity ultrasound (US) propagating through a steel mold on the microstructure and mechanical properties of die-cast AlSi9Cu3, for different levels of electric power and at different distances to the waveguide/mold interface. The influence of those parameters on the morphology of -Al and eutectic Si and on the volume of porosity were investigated and characterized. The morphological characterization revealed that the high intensity vibration not only promoted the formation of small -Al globular grains but also modify the eutectic silicon, as well as decreased the volume of porosity. Besides microstructure modification, US treatment improved the alloy mechanical properties, namely UTS and strain, which maximum values were 339 MPa and 2.9% respectively by comparison to the values obtained for castings produced without US vibration. A mechanism of eutectic Si modification based on theoretical-experimental analysis is proposed